The gender category in linguistic communication (in Polish and Russian legal texts) - Borys, Iwona; Nawacka, Joanna (Papers in Linguistics, 2023)
The category of gender, which is a set of different human characteristics, is reflected in language. The purpose of this article is to present and discuss the category of gender in interpersonal communication with reference to Polish and Russian legal texts. Legal texts identify a human being as a citizen of a certain state and community and regulate their functioning within a given group. As by law all citizens are to receive equal treatment, the gender category is not a criterion for the choice of legal responsibility, although examples of linguistic gender differentiation can be noted in both the Polish and Russian legal systems. The selected texts of constitutions and collections of legal acts were examined with the use of qualitative and quantitative linguistic analysis in order to excerpt gender-indicating lexemes in both languages, and to examine their equivalence and translatability into the other language. Results show a similar stock of words expressing the gender category in Polish and Russian legal language. Nominalizations denoting female and male genders extracted from the legal texts undergoing scrutiny do not pose a particular translation problem; their equivalents can be found in the standard language and in bilingual dictionaries.